Exploring the perceptions and experiences of community health workers using role identity theory - Langelihle Mlotshwa; Bronwyn Harris; Helen Schneider; Mosa Moshabela (Taylor & Francis Group, 2015)
Background: Community health workers (CHWs) are an integral resource in many health systems, particularly in resource-poor settings. Their identities - 'who' they are - play an important role in their hiring, training, and retention. We explore the perceptions, experiences, and identities of CHWs as they adopt a CHW role in rural South Africa, using 'role identity theory'. Design: From April to December 2010, we conducted 18 semi-structured interviews with CHWs volunteering in non-governmental home-based care (HBC) organisations in one rural sub-district in South Africa. The role identity theory framework was used to understand the work of CHWs within their communities, addressing themes, such as entry into, and nature of, caring roles, organisational support, state resourcing, and community acceptability. A thematic content analysis was used to analyse the collected data. Results: The study found that CHWs usually begin their 'caring work' before they formally join HBC organisations, by caring for children, neighbours, mothers, fathers, friends, and the community in some way. CHWs felt that becoming a health worker provided an elevated status within the community, but that it often led community members to believe they were able to control resources. The key role identities assumed by CHWs, as they sought to meet patients' and their own needs, were a complex mix of community 'insider', 'outsider', and 'broker'. Each of these role identities served as a unique way to position, from the CHW's perspective, themselves and the community, given the diversity of needs and expectations. Conclusions: These role identities reveal the tensions CHWs face as 'insider' members of the community and yet at times being treated as 'outsiders', who might be regarded with suspicion, and at the same time, appreciated for the resources that they might possess. Understanding role identities, and how best to support them, may contribute to strategies of retention and sustainability of CHW programmes, as their formalisation in different contexts continues to grow.